A feast for crows [compact disc, unabridged] - Martin, George R. R. (Martin, George R. R. Song of ice and fire, 2011)
After centuries of strife, the seven powers dividing the land have worn themselves down into a stalemate. The monstrous King Joffrey is dead, and the Northern rebels are scattered. Into this blasted peace, however, come the scavengers, outlaws and renegades, who have been waiting to pick over the remnants. Daring new plots and alliances are formed, and personalities new and old have emerged from the struggle to take up new positions.